Anti-cancer drug sensitivity testing and preclinical evaluation of the anti-cancer potential of WEE1 inhibitor in triple-negative breast cancer patient-derived organoids and xenograft models - Seungyeon Ryu; Hoe Suk Kim; Sangeun Lee; So-Hyun Yoon; Moonjou Baek; A Young Park; Han-Byoel Lee; Ga Yeon Kim; Kyung Hyeun Park; Ji-Jung Jung; Yireh Han; Dong Woo Lee; et al. (Breast Cancer Research)
Abstract Background Relevant surrogates that maintain the pathological and physiological properties of patient tumors are essential for guiding triple-negative breast cancer (TNBC) therapy. The goals are to generate patient-derived organoids (PDOs), xenografts (PDXs), and PDX-derived organoids (PDXOs), evaluate the therapeutic potential of the WEE1 inhibitor AZD1775, and compare their responses to 18 anti-cancer drugs in PDOs and PDXOs. Methods PDOs were produced from surgical specimens of patients with TNBC. PDXs were generated by transplanting PDOs into the mammary fat pads of NOD.Cg-Prkdcscid Il2rgtm1wjl/SzJ mice. PDXOs were derived from fresh tumor specimens of PDXs. For drug efficacy, half-maximal inhibitory concentration (IC50) values for 18 anti-cancer drugs on PDOs and PDXOs were calculated using the CellTiter-Glo® 3D cell viability assay in a high-throughput drug screening system. The relationship between WEE1 expression and survival in TNBC-basal-like (BL) patients was analyzed using the Kaplan–Meier Plotter database. Mice were treated with AZD1775 via oral gavage (30 mg/kg). Biological mechanisms underlying the anti-cancer drug responses were evaluated by calcein-AM staining, caspase 3/7 staining, Western blot, flow cytometry, and immunohistochemistry. Results PDOs were established through subcultures of 2-7 passages. TNBC-BL PDXs expressing CK5, vimentin, and EGFR were generated and expanded over 3-4 generations of transplantation. PDXOs were produced through subcultures of 4-5 passages. PDOs, PDXs, and PDXOs retained the immunohistological characteristics of the relevant patients with TNBC. WEE1 was associated with poor survival outcomes in TNBC-BL patients. The highest cytotoxicity and tumor growth suppression to AZD1775 therapy were observed in PDXOs and PDXs with high WEE1 expression. AZD1775 inhibited WEE1 and CDK1 phosphorylation, increased γH2AX phosphorylation, induced G2/M arrest, and activated caspase 3/7 in PDXOs and PDXs, all associated with DNA damage, mitotic catastrophe, and apoptosis. Anti-cancer drug responses were highly concordant between matched PDOs and PDXOs. The responses of PDOs and PDXOs to anti-cancer drugs were comparable to those of patients receiving neoadjuvant or adjuvant chemotherapy, according to clinical records. Conclusion PDOs, PDXOs, and PDXs, which maintained the immunological properties of TNBC patient, provide a scientific rationale for future WEE1-targeted clinical trials in TNBC. PDOs and PDXOs represent cost- and time-effective surrogates for predicting prioritized personalized therapy.